2015
DOI: 10.1155/2015/201641
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Carotenoids in Four Species ofTrentepohlia(Trentepohliales, Chlorophyta)

Abstract: Trentepohlia Martius, a dominant green subaerial alga, grows abundantly in Shillong and imparts the yellow, red, and orange colours to most of the tree barks, walls, rocks, and electric poles because of high accumulation of carotenoids in their filaments. This study emphasised the seasonal changes in carotenoid content amongst four different species of Trentepohlia, that is, T. diffracta, T. arborum, T. umbrina, and T. abietina, collected from four different substrata, that is, wall, rock, electric pole, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Mukherjee et al (2010) studied two species of Trentepohlia from natural habitats in Assam State, India, and found that the total carotenoid content in both species was very high, with a small amount of chlorophyll. Kharkongor and Ramanujam (2015) studied the accumulation of total carotenoids in four Trentepohlia species in Shillong, India, and found a high accumulation of carotenoids (especially β-carotene) in their filaments.…”
Section: Pigment Content Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mukherjee et al (2010) studied two species of Trentepohlia from natural habitats in Assam State, India, and found that the total carotenoid content in both species was very high, with a small amount of chlorophyll. Kharkongor and Ramanujam (2015) studied the accumulation of total carotenoids in four Trentepohlia species in Shillong, India, and found a high accumulation of carotenoids (especially β-carotene) in their filaments.…”
Section: Pigment Content Variabilitymentioning
confidence: 99%
“…Scientists around the world have been trying to collect, extract, and isolate β-carotene from Trentepohlia (Aburai et al, 2013;Chen et al, 2015), but no one has done it yet in Thailand. Kharkongor and Ramanujam (2015) and Mukherjee et al (2010) reported that β-carotene content could vary in species across different seasons because of the different environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since presence of high quantity of carotenoids in these four species of Trentepohlia had also been reported [33], the antioxidant activities contributed by carotenoids besides flavonoids must not be ruled out in this case. Martinez & Barbosa [50] reported the ability of carotenoids to deactivate singlet oxygen by physical quenching.…”
Section: Discussionmentioning
confidence: 88%
“…A total number of 10 species had been reported [32], of which four species were dominant. Presence of high quantity of carotenoids was also documented from these four species of Trentepohlia [33]. Hence, this present work was carried out to examine specifically the antioxidant activity of the four dominant species and to throw to light the participation of other antioxidant compounds such as phenolics besides the well known carotenoids.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation